Những câu hỏi liên quan
Hoàngg Chii
Xem chi tiết
Phía sau một cô gái
18 tháng 1 2022 lúc 16:43

A = 6 + 6+ 63 + 6+....+ 62020

6A = 6+ 63 + 6+ 65 +....+ 62021

⇒ 6A - A = ( 6+ 63 + 6+....+ 62021 ) - ( 6+ 63 + 6+....+ 62020 )

⇒ 5A = 62021 - 6

Ta có:  6n = 5A + 6

⇔        6n = 62021 - 6 + 6

⇔         6n = 62021

⇔         n = 2021

Bình luận (0)
mai ngoc khanh doan
Xem chi tiết
bảo nam trần
23 tháng 12 2016 lúc 11:20

A = 6 + 62 + 63 + 64 + ... + 62016

6A = 62 + 63 + 64 + 65 + ... + 62017

6A - A = (62 + 63 + 64 + 65 + ... + 62017) - (6 + 62 + 63 + 64 + ... + 62016)

5A = 62017 - 6

6n = 5A + 6

6n = (62017 - 6) + 6

6n = 62017

=>n = 2017

Bình luận (0)
Phạm Vương Bảo Ngọc
Xem chi tiết
ILoveMath
14 tháng 11 2021 lúc 10:35

61.B

62.x=5

63.D

64.C

Bình luận (1)
Quân Lưu Minh
Xem chi tiết
Kim Châu
Xem chi tiết
Nguyễn Huy Tú
20 tháng 12 2016 lúc 18:09

Ta có:

A = 6 + 62 + 63 + 64 + ... + 62016

=> 6A = 62 + 63+ 64 + ... + 62017

=> 6A - A = ( 62 + 63 + 64 + ... + 62017 ) - ( 6 + 62 + 63 + 64 + ... + 62016 )

=> 5A = 62017 - 6 (1)

Thay (1) vào 6n = 5A + 6

=> 6n = 62017 - 6 + 6

=> 6n = 62017

=> n = 2017

Vậy n = 2017

Bình luận (0)
Nguyễn Hương Giang
Xem chi tiết
nguyễn văn hiệp
Xem chi tiết
Võ Thành Huy
Xem chi tiết
Giang Nguyen
26 tháng 12 2020 lúc 14:50

Chó

Bình luận (0)
Lê Quang
Xem chi tiết
Lê Quang
Xem chi tiết
Mac Willer
5 tháng 5 2021 lúc 22:25

n thuộc N hay Z

Bình luận (1)